HR practices and deviant behavior at work: An exploratory study - Mohd Shamsudin, Faridahwati; Subramaniam, Chandrakantan; Ibrahim, Hadziroh (IACSIT Press, Singapore., 2011)
The study sought to explore the influence of HR practices on deviant workplace behavior among st 372 manufacturing employees in the northern region of Malaysia.Results show that all dimensions of HR practices i.e. job description; employment security, internal career opportunities, and result-oriented appraisal were negatively related to deviant behavior at work.The implication of the study is discussed.